India Amidst COVID-19 Crisis: The Good, The Bad and The Ugly - Negi, Sanjay Singh (Journal of Lumbini Medical College, 2020)
Beating the statistics: With a population of over a billion, high population density with overcrowding especially in metropolis and underdeveloped health infrastructure, the projections for corona virus disease (COVID-19) pandemic were not in favour of India. Most statistical models had predicted over 5 lakh cases and more than 38,000 deaths and warned that India must prepare for a tsunami of COVID-19 cases. The situation appeared to be grimmer given that the incidence of diabetes, hypertension and respiratory diseases due to tuberculosis and air pollution is higher amongst Indians which are known risk factors for severe disease and death due to COVID-19.